2021
DOI: 10.3390/ani11041076
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Long-Acting Injectable Selenium Preparation Administered to Pregnant Ewes and Lambs

Abstract: The aim of this study was to evaluate the effects of a long-acting selenium (Se) preparation administered to sheep. The experiment was conducted on 30 dams and 36 lambs divided into three equal groups of 10 dams and 12 lambs each: Control—C, and two experimental groups—E (Se administered to pregnant ewes) and EI (Se administered directly to lambs after the colostral period). The Se preparation (Barium Selenate Injection, BVP Animal Care, 50 mg/mL) was administered by injection at 1 mL/50 kg (1 mg Se/kg) body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…Much lower results were obtained by Pilarczyk et al [ 41 ] and Karimi-Poor et al [ 42 ], 13 µg/L and 28 µg/L, respectively. The current study revealed an improvement in the Se status of ewes administered barium selenate in the 3rd month of pregnancy, which is consistent with the results obtained by Milewski et al [ 30 ] in a study of Pomeranian sheep.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Much lower results were obtained by Pilarczyk et al [ 41 ] and Karimi-Poor et al [ 42 ], 13 µg/L and 28 µg/L, respectively. The current study revealed an improvement in the Se status of ewes administered barium selenate in the 3rd month of pregnancy, which is consistent with the results obtained by Milewski et al [ 30 ] in a study of Pomeranian sheep.…”
Section: Discussionsupporting
confidence: 93%
“…Experimental group lambs were characterized by a faster growth rate and better muscle development. The same effects were noted in an earlier study by Milewski et al [ 30 ]. Moreover, similar results were obtained by Muñoz et al [ 38 ] who found that an injection of barium selenate administered to ewes enhanced the growth rate of their lambs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations